Determinants of Non-Performing Financing of Mortgage in Islamic Commercial Banks - Hasanah, Rofadatul; Dina Fitrisia Septiarini; Dian Filianti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This study aims to determine the effect of Capital Adequacy Ratio, Return on Assets, BI 7-Day Rate, and Inflation towards Non-Performing Financing Mortgages in Islamic commercial banks in Indonesia. The population of this study is the Islamic commercial banks in the period 2015-2019. The sample used is a saturated sample, which uses all Islamic banks as research samples. This research uses a quantitative approach using time series data. All variables use the percentage of growth and show the results of the level stationary so that the technique used is Ordinary Least Square (OLS) regression analysis which is processed using E-Views 10 software. The results of this study indicate partially the Capital Adequacy Ratio and Return on Assets variables have a negative influence significant to Non-Performing Financing Mortgages. While BI 7-Day Rate and Inflation variables do not influence Non- Performing Financing Mortgages. Nonetheless, Capital Adequacy Ratio, Return on Assets, BI 7-Day Rate, and Inflation simultaneously have a significant effect on the Non-Performing Financing of Mortgages in Islamic commercial banks in Indonesia in the period 2015-2019